Alfalfa mosaic virus (AMV): genetic diversity and a new natural host - Trucco, Veronica Milagros; Castellanos Collazo, Onias; Vaghi Medina, Carlos Gaston; Cabrera Mederos, Dariel; Lenardon, Sergio Luis; Giolitti, Fabian (Springer, 2021)
Alfalfa mosaic virus (AMV) is a plant virus belonging to the genus Alfamovirus in the family Bromoviridae. AMV occurs worldwide and is one of the most important viruses affecting a large number of plant species, mainly commercially important crops. In this study, we report the molecular analysis of the CP gene sequences of 23 AMV isolates obtained from different geographical areas and hosts: alfalfa (Medicago sativa), kidneyweed (Dichondra repens), red clover (Trifolium pratense) and Lavandin Super (Lavandula angustifolia x L. latifolia). The comparison among the Argentine CP sequences showed identity values ranging from 95.6 to 100% at the nucleotide level and from 95.9 to 100% at the predicted amino acid level. Phylogenetic studies based on complete nucleotide sequences of CP showed that all Argentine isolates were included in subgroup I of AMV isolates, along with other isolates from alfalfa. No clear relationship between AMV isolates and geographical or host origin was observed. This is the first report of kidneyweed as a natural host of AMV worldwide, and of AMV infection in red clover and Lavandin Super in Argentina. This work provides more evidence of CP variability between AMV isolates and presents a new AMV plant host, expanding the host range of this virus. Therefore, AMV represents a threat to the successful production of several economically important crops in Argentina. Further studies are necessary for a better understanding of the role of these host species in AMV epidemiology.